2021
DOI: 10.1088/1361-6528/ac3a38
|View full text |Cite
|
Sign up to set email alerts
|

High polarization and wake-up free ferroelectric characteristics in ultrathin Hf0.5Zr0.5O2 devices by control of oxygen-deficient layer

Abstract: The formation of an interfacial layer is believed to affect the ferroelectric properties in HfO2 based ferroelectric devices. The atomic layer deposited devices continue suffering from a poor bottom interfacial condition, since the formation of bottom interface is severely affected by atomic layer deposition and annealing process. Herein, the formation of bottom interfacial layer was controlled through deposition of different bottom electrodes (BE) in device structure W/HZO/BE. The transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
1
26
1
Order By: Relevance
“…These results indicate that EPA could potentially be used to reduce the dose of the wake-up treatment in HZO; however, the effectiveness of treatment would depend largely on processing conditions. Researchers have previously created WUF-HZO by optimizing the electrode/HZO interface by selecting a different electrode material 42 or by reducing the concentration of defects within the HZO by optimizing the ALD process. 43 X-ray photoelectron spectroscopy (XPS) has revealed that achieving a wake-up free state involves altering the state of oxygen in the HZO.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These results indicate that EPA could potentially be used to reduce the dose of the wake-up treatment in HZO; however, the effectiveness of treatment would depend largely on processing conditions. Researchers have previously created WUF-HZO by optimizing the electrode/HZO interface by selecting a different electrode material 42 or by reducing the concentration of defects within the HZO by optimizing the ALD process. 43 X-ray photoelectron spectroscopy (XPS) has revealed that achieving a wake-up free state involves altering the state of oxygen in the HZO.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure 7(b) and (c) show the polarization−voltage (P−V) and current density−voltage (J−V) curves of the Hf 0.5 Zr 0.5 O 2 thin film deposited on the MoO x and TiN electrodes, respectively. 71 Here, 0, 5, 10, and 15% flow rates of the oxygen gas in-flow, which affect the relative ratio of oxygen gas 72 The Hf 0.5 Zr 0.5 O 2 thin film deposited on the W or IrO 2 electrode shows a higher P r than that of the Hf 0.5 Zr 0.5 O 2 thin film on the TiN electrode. It has been suggested that W and the IrO 2 bottom electrode effectively suppress the formation of nonferroelectric ILs and/or decrease the oxygen vacancy concentration.…”
Section: Strategies To Resolve the Current Issuesmentioning
confidence: 99%
“…Figure (d) and (e) show the P – V and I – V curves of the Hf 0.5 Zr 0.5 O 2 thin film deposited on the W, Pt/W, IrO 2 , and TiN bottom electrodes, respectively, with the top electrode material being all W . The Hf 0.5 Zr 0.5 O 2 thin film deposited on the W or IrO 2 electrode shows a higher P r than that of the Hf 0.5 Zr 0.5 O 2 thin film on the TiN electrode.…”
Section: Electrode–ferroelectric Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various devices are utilized in VMM, from a typical transistor to novel synaptic devices. 5,6,10,[12][13][14][15][16][17][18][19] A greater number of parallel connections can improve computation performance as the dot product is conducted by the parallel connections between the processing unit (logic device) and memory. Therefore, a large number of logic and memory devices must be integrated together in parallel.…”
Section: Introductionmentioning
confidence: 99%